2007
DOI: 10.1037/0021-843x.116.1.166
|View full text |Cite
|
Sign up to set email alerts
|

Gender bias in diagnostic criteria for personality disorders: An item response theory analysis.

Abstract: The authors examined gender bias in the diagnostic criteria for Diagnostic and Statistical Manual of Mental Disorders (4th ed., text revision; American Psychiatric Association, 2000) personality disorders. Participants (N=599) were selected from 2 large, nonclinical samples on the basis of information from self-report questionnaires and peer nominations that suggested the presence of personality pathology. All were interviewed with the Structured Interview for DSM-IV Personality (B. Pfohl, N. Blum, & M. Zimmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 43 publications
8
67
3
1
Order By: Relevance
“…This suggests that women tend to perceive their health as better than it actually is: that is, having an optimistic view of their health status. This finding is in contradiction to previous research that found that women were prone to overreporting of mental health symptoms (Jane et al 2007;Sigmon et al 2005), and suggests a possible reversal of response bias functioning between self-reported health indicators and mental health items. On the contrary, men appear to perceive their health status as worse than it actually is and, hence, overreporting health symptoms.…”
Section: Discussioncontrasting
confidence: 84%
“…This suggests that women tend to perceive their health as better than it actually is: that is, having an optimistic view of their health status. This finding is in contradiction to previous research that found that women were prone to overreporting of mental health symptoms (Jane et al 2007;Sigmon et al 2005), and suggests a possible reversal of response bias functioning between self-reported health indicators and mental health items. On the contrary, men appear to perceive their health status as worse than it actually is and, hence, overreporting health symptoms.…”
Section: Discussioncontrasting
confidence: 84%
“…Differential Item Functioning (DIF) has been previously reported for 3 of the ASPD criteria (Jane et al 2007). DIF with respect to sex means that one sex endorses a specific criterion differently from the other sex despite adjusting for possible differences in the overall (or ‘latent’) ASPD between the sexes (Penfield and Camilli 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Dependent, histrionic, and borderline PDs occur more often in female patients whereas antisocial, narcissistic, and obsessive-compulsive PDs occur more often in male patients (Anderson et al, 2001). The DSM IV-TR makes no statement regarding sex bias among the PDs, but it does suggest that six disorders (antisocial, narcissistic, obsessive-compulsive, paranoid, schizotypal, schizoid) are more prevalent in men, and three others (borderline, histrionic, dependent) occur more in women (Jane et al, 2007). The diagnosis schizoid PD (SPD) is more common in men (Fulton and Winokur, 1993), whereas borderline PD (BPD) is more often diagnosed in women than in men (De Moor et al, 2009).…”
mentioning
confidence: 91%